Pharmacists Becoming Physicians: For Better or Worse? - Eugene Y. H. Yeung (MDPI AG, 2018)
Physicians and pharmacists nowadays are often described as adversaries rather than members of the same team. Some pharmacists apply to medical school later in their careers, and experience obstacles during the transition process. This article details interviews with two physician–pharmacists, who each have a past pharmacist license and current physician license. The respondents described the limitations of pharmacists’ scope of practice as their main reasons to pursue a medical career. However, the respondents enjoy applying their pharmacy knowledge and experience to improve their medical practice. They do not feel pharmacy seniors and medical recruiters are supportive towards their chase for medical careers. The respondents noted the importance of peer-reviewed articles to promote pharmacist involvement in patient care and collaboration between physicians and pharmacists. Conflicts between physicians and pharmacists tend to happen because of their different focuses on patient care. The respondents do not see themselves having an edge over other medical school applicants, and noted that recruiters could negatively view their pharmacy experience. The respondents believe that physician–pharmacists are catalysts to foster collaboration between physicians and pharmacists, because they clearly understand the role of each profession. Nevertheless, the respondents feel that physicians and pharmacists are generally lukewarm towards pharmacists transitioning into physicians.